2020
DOI: 10.1097/sap.0000000000002319
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Tip Rotation by Exclusive Superficial Musculoaponeurotic System Deep Medial Ligament Management

Abstract: The nasal tip constitutes the mobile portion of the nose, in direct contraposition to the pyramid that is a fixed structure. Its configuration, position, and shape are derived mainly from the outline and from the thickness of the wing cartilages, important elements of the nasal tip, that together with skin and subcutaneous tissue can deeply influence the configuration and dynamics of this section of the nose as well. In reshaping the nasal tip, 2 fundamental concepts must be considered: projection and rotation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…The results of this study support the findings of other authors [ 29 , 30 ] who reported five layers of the nasal region, which are: the subcutaneous fatty layer, the fibromuscular layer, the profound fatty layer, the fibrous longitudinal layer, and a layer that contains interdomal ligaments. We consider that, at this level, the SMAS is represented by a second layer: a fibromuscular one, which interconnects with the alar muscles and distributes power to the dermis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study support the findings of other authors [ 29 , 30 ] who reported five layers of the nasal region, which are: the subcutaneous fatty layer, the fibromuscular layer, the profound fatty layer, the fibrous longitudinal layer, and a layer that contains interdomal ligaments. We consider that, at this level, the SMAS is represented by a second layer: a fibromuscular one, which interconnects with the alar muscles and distributes power to the dermis.…”
Section: Discussionsupporting
confidence: 92%
“…This was also observed during the dissection of specimens. At the base of the nasal pyramid, it appears that the superficial and deep fascia are joined in a dense connective structure, most likely the dermocartilaginous ligament [ 29 , 50 ]. To the medial side of the nasolabial groove, the superficial fascia becomes more obvious and mediates the cutaneous insertion of the zygomatic muscles.…”
Section: Discussionmentioning
confidence: 99%
“…16 Its surgical section, alone, determines nasal tip rotation. 17 The Pitanguy ligament is the main structural component of our interalar ligament flap. Its preservation and subsequent reattachment during rhinoplasty were previously cited in the literature 3,6,8,18 with conclusions mainly supported by experience (such as those on reduced swelling, tip rotation/ projection stabilization) or absence of a control group.…”
Section: Discussionmentioning
confidence: 99%